Respuestas

¡La mejor respuesta!
  • Usuario de Brainly
2013-05-27T21:06:19+02:00
Formulas
(a+ b)² = a² + 2ab + b²
(a+b)³ = a³ + 3a²b + 3ab² + b³
vamos a plicar la formual a cada uno para resolver
A)    (x+2)²  = x² + 2.2x + 2²
        (x +2)² = x² + 4x + 4

b)    (x-3)³ = x³ - 3x²3 + 3x(3)²  - 3³
       (x-3)³ = x³ - 9x² + 27x - 27

c)    (x+y)² = x² + 2xy + y²

d)   (3x+1)³ = (3x)³ + 3(3x)²1 + 3(3x)1² + 1³
     
(3x+1)³ = 27x³ + 27x² + 9x + 1

e)   (2y-2)² = 4y²  - 8y + 4

f)   (1/2x-1)³  = (1/2x)³ -3(1/2x)² + 3(1/2x).1² - 1³
   
(1/2x-1)³  = 1/8x³ - 3/4x² + 3/2x - 1

  
g)   (x+y)² = x² + 2ay +y²

h)  (2/3x + 1/2)³ = (2/3x)³ + 3(2/3x)²(1/2)+ 3(2/3x)(1/2)² + (1/2)³
   
(2/3x + 1/2)³ = 8/27x³ + 2/3x² + 1/2x + 1/8

i)   (5x – 1/3)²  = (5x)² - 2(5x)(1/3) + (1/3)²
     (5x – 1/3)²  = 25x² - 10x/3 + 1/9

j)   (2/3x – 1/2)³ =
(2/3x)³ - 3(2/3x)²(1/2)+ 3(2/3x)(1/2)² - (1/2)³
   
(2/3x -  1/2)³ = 8/27x³ -2/3x² + 1/2x -  1/8


espero que te sirva, salu2!!!!